A descriptor for the design of 2D MXene hydrogen evolution reaction electrocatalysts. Issue 35 (22nd August 2022) - Wang, Changxin; Wang, Xiaoxu; Zhang, Tianyao; Qian, Ping; Lookman, Turab; Su, Yanjing
Abstract : MXene-STM design flow: A physical descriptor ϕ is built to uncover the hydrogen evolution reaction (HER) trends in Ti2 CO2 -STM (single transition metal doping) catalysis. Abstract : The two-dimensional metal carbide semiconductor, Ti2 CO2, is recognized as having considerable potential as a cost-effective basal plane electrocatalyst for the hydrogen evolution reaction (HER). However, challenges in terms of both catalytic activity and conductivity still remain. The HER catalytic activity of 2D Ti2 CO2 can be tuned by Ti vacancies (VTi ) anchoring single transition metal (STM) atoms. Herein, 27 different Ti2 CO2 -STMs (STM = 3d, 4d, 5d metals) and 81 HER catalytic active sites are screened by computational methods. The results indicate that STM doping not only optimizes the Gibbs free energy of hydrogen adsorption (Δ G H ), but also converts semiconductors into conductors. Several new and promising nonprecious HER electrocatalysts are identified, including Ti2 CO2 –W. The excellent catalytic activity (Δ G H ≈ 0 eV), conductivity, and stability make it an ideal potential catalyst for the HER. The p–d orbital hybridization between STM and C and O atoms leads to a rearrangement of electrons near the Fermi level, which plays a crucial mechanism in regulating HER activity. We apply machine learning methods to build a physical descriptor to uncover trends in Ti2 CO2 -STM HER catalysis, and the descriptor can also be applied to Zr2 CO2 -STM and Ta2 CO2 -STM HER catalysis. This work provides a promising strategy for improving the HER performance of 2D Ti2 CO2, and more importantly, develops simple descriptors to efficiently search for highly active HER catalysts.